miR-107-enriched exosomes promote ROS/wnt/autophagy, inhibit intracellular mycobacterial growth and attenuate lung infection - Xu, Wei; Wu, Yuan; Yang, Min; Zhou, Jiayu; Zhu, Liying; Ma, Xiaosai; Qiu, Chonghai; Shen, Ling; Shen, Hongbo; Wang, Feifei (Frontiers in Immunology, 2025)
Exosomes, known as small membrane vesicles of endocytic origin produced by most cell types, exist in a variety of body fluids including plasma. The roles of exosomes in immune responses against Mycobacteria tuberculosis (Mtb) infection remain poorly characterized. Here, we found that miR-107 highly expressed in exosomes from plasma of TB patients but not healthy control (HC) subjects. Consistently, such miR-107-high exosomes were also detected in both the extracellular fluid released by mycobacterial-infected macrophages and the plasma of mycobacterial-infected mice. Interestingly, adding the miR-107-high plasma exosomes or the miR-107 mimics to infected THP-1 macrophages inhibited intracellular mycobacterial growth. Consistently, while nanoscale and fluorescence imaging revealed that miR-107 could be transferred inter-cellularly via exosomes, miR-107-enriched exosomes from miR-107 overexpressing cells also inhibited mycobacterial growth in THP-1 macrophages and primary monocytes/peripheral blood mononuclear cells (PBMC). Mechanistically, miR-107-high exosomes increased ROS production; miR-107 regulated Wnt pathway by targeting Wnt16 and promoted autophagy in THP-1 macrophages. Furthermore, treatment of infected mice with miR-107-enriched exosomes reduced mycobacterial infection in lung tissues. Our results raise a possibility to explore miR-107-high plasma exosomes for a potential surrogate marker for TB. Findings suggest that exosomes enriched with miR-107 or other bio-active molecules may potentially serve as an attractive approach for treatment of infection.